2014
DOI: 10.4315/0362-028x.jfp-14-132
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and Meteorological Factors Associated with Isolation of Listeria Species in New York State Produce Production and Natural Environments

Abstract: Listeria species have been isolated from diverse environments, often at considerable prevalence, and are known to persist in food processing facilities. The presence of Listeria spp. has been suggested to be a marker for Listeria monocytogenes contamination. Therefore, a study was conducted to (i) determine the prevalence and diversity of Listeria spp. in produce production and natural environments and (ii) identify geographical and/or meteorological factors that affect the isolation of Listeria spp. in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 41 publications
11
103
4
Order By: Relevance
“…Moreover, slope gradients have been reported to impact the detection of Listeria in water samples [35,37,67]. We found no indication that pelagic cell counts of Listeria are higher than cell counts on water plants and in sediment at all areas sampled.…”
Section: Year-round Occurrence Of the Genus Listeriacontrasting
confidence: 70%
See 2 more Smart Citations
“…Moreover, slope gradients have been reported to impact the detection of Listeria in water samples [35,37,67]. We found no indication that pelagic cell counts of Listeria are higher than cell counts on water plants and in sediment at all areas sampled.…”
Section: Year-round Occurrence Of the Genus Listeriacontrasting
confidence: 70%
“…While a higher occurrence in fall, winter and spring periods was observed [40,42,43,71], contrary findings with a higher occurrence of Listeria spp. in the summer months have also been reported [37,72]. The overall species compositions of Listeria populations of water, water plants and sediments are shown in Figure 2.…”
Section: Biodiversity Of Listeria At the Species Levelmentioning
confidence: 72%
See 1 more Smart Citation
“…2). Previous work also has shown that generic E. coli (18), E. coli O157:H7 (27), Salmonella (28), and Listeria (29,30) are positively associated with livestock density or proximity to livestock. Similarly, studies that have aggregated reported EHEC illnesses to county or district levels have generally observed higher EHEC infection rates in counties with higher cattle densities, although this approach infers rather than directly links cases and exposures (19,20).…”
Section: Discussionmentioning
confidence: 85%
“…was conducted as described in Chapin et al (2014). We replicated the random forest analysis of environmental distribution by independently obtaining and processing spatial and meteorological GIS predictor data ( Table 2).…”
Section: Materials and Methods (Page 3; First Paragraph)mentioning
confidence: 99%